COURSE OF LIFE CHILDREN ENTERING STYLE OF PHYSICAL EDUCATION FEDERAL UNIVERSITY OF PIAUÍ, IN PERIODS 2014.2 AND 2015.1 (Fiep Bulletin - online, 2016)
The society is concerned more and more with health, it is proven that how an individual lives routinely directly influences the health of an individual, so the lifestyle has become an important health evaluation criterion. The aim of this study was to investigate the lifestyle of students entering the course of Physical Education in the periods 2014.2 and 2015.1 of the Federal University of Piauí. A sample of 82 university students with a mean age of 20.32 years (? = 3.82) of both sexes. For data collection was used questionnaire Pentacle Welfare to assess the lifestyle, classifying them as negative, regular and positive. The questionnaire included five factors that influence the lifestyle, they are: nutrition, physical activity, preventive behavior, social relationships and stress management, which were listed individually and in general. Data analysis was performed by descriptive statistics. The conclusion, considering the factors individually, the evaluated students have positive rating factors in physical activity and social interaction, since the nutrition factors, preventive behavior and stress management presented regular classification, beyond the general classification which was also characterized as regular. It is suggested to improve the interventional measures lifestyle addressing mainly classified with regular strategies.
Keywords: Lifestyle; Physical Education; Health